Medicinal plants of traditional use in the southern region of Pará used during the Covid-19 pandemic (Research, Society and Development, 2022)
As a result of the pandemic, the use of homemade medicines has spread even more in society, taking into account the harmfulness of self-medication, this study aimed to evaluate which medicinal plants were the most used during the pandemic for treatment and/or homemade prevention of the Coronavirus . The research is characterized as descriptive with a quantitative approach. Taking into account the pandemic, the study was carried out in a non-face-to-face manner, through a questionnaire on Google Forms. The research was carried out with 200 people, 150 women and 50 men, predominantly brown people with 137 in total and also with a predominant age group between 18 and 26 years old. It was possible to identify that among the most used medicinal plants boldo, ginger, garlic and saffron stand out. It was also observed that the use of these plants was usually directed to teas. In this way, the discussion of the topic is important today, because the pandemic has changed the routine of society and the way in which health is perceived, so that to avoid agglomerations, several people preferred to take home remedies and not seek a health unit, thus understanding the use of home remedies has become fundamental.